2008
DOI: 10.1080/15534510802341124
|View full text |Cite
|
Sign up to set email alerts
|

And now for something completely different? The impact of group membership on perceptions of creativity

Abstract: A wealth of historical, cultural and biographical evidence points to the fact that there is considerable variation in different people's judgements of creative products. What is creative to one person is deviant to another, and creative efforts often fail to be given the enthusiastic reception that their creators anticipate and think they deserve. Unpacking the roots of these discrepancies, this paper develops an analysis of creativity that is informed by the social identity approach. This analysis is supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…What that can mean is that group members are then more likely to be creative in the same type of way as their group and stick to the established social norms (Adarves-Yorno, Postmes, & Haslam, 2007). Further, people who are part of the group are rated as more creative than non-group members (Adarves-Yorno, Haslam, & Postmes, 2008;S. A. Haslam, Adarves-Yorno, Postmes, & Jans, 2013).…”
Section: Creativity Vs Conscientious: Improvementmentioning
confidence: 99%
“…What that can mean is that group members are then more likely to be creative in the same type of way as their group and stick to the established social norms (Adarves-Yorno, Postmes, & Haslam, 2007). Further, people who are part of the group are rated as more creative than non-group members (Adarves-Yorno, Haslam, & Postmes, 2008;S. A. Haslam, Adarves-Yorno, Postmes, & Jans, 2013).…”
Section: Creativity Vs Conscientious: Improvementmentioning
confidence: 99%
“…For example, Schimmel and Förster () found that a high temporal distance prime enhanced the acceptance of unconventional art, likely due to inclusive categorization eminent to high level construals that people formed of these targets under conditions of psychological distance (e.g., Liberman & Trope, ). Moreover, research by Adarves‐Yorno, Postmes, and Alexander Haslam (); Adarves‐Yorno, Alexander Haslam, and Postmes () evidences that evaluations of creativity are in part shaped by ingroup norms to which the creative expressions need to conform. Thus, people's evaluations of the creative work of others are partly shaped by situational factors, reflecting that perceptions of creativity are indeed malleable by factors unrelated to the creative process.…”
Section: Contextual Dependency Of Valuing Creative Artmentioning
confidence: 99%
“…novelty (Boden, 2004;Epstein, 1991;Perkins 1994;Smith, 2005) and whether social values and recognition biases interfere with attributions of creativity (Adarves-Yorno, Postmes and Haslam, 2006;Adarves-Yorno, Haslam and Postmes, 2008;Charyton, Basham and Elliot, 2008;Corazza, 2016;Kasof, 1995;Ludwig, 1995;Runco, 1995).…”
mentioning
confidence: 99%
“…Problems within three concepts of the standard definition have been identified: the nature of novelty, the role of effectiveness, whether defined through adaptivity or values, and whether recognition is necessary to the existence of creativity. These problems have received significant attention during seven decades of research but remain unresolved (Adarves-Yorno, Haslam and Postmes, 2008;Boden, 2004;Kasof, 1995; Kaufman and Baer, 2012;Runco and Jaeger, 2012;Stein, 1974;). Starting with novelty, there are two philosophical conundrums.…”
mentioning
confidence: 99%
See 1 more Smart Citation